MODEL PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MINUMAN LIDAH BUAYA DI PONTIANAK - Makeas, Herianto; Nurliza, Nurliza; Imelda, Imelda (Jurnal Sains Mahasiswa Pertanian, 2019)
The result of aloe vera beverage production Pontianak unable to compete with the brand of outside Pontianak or the beverage substitutes, because of defective design and quality or the product picture. The study aims to design a model of consumers preference toward the resolution to purchase aloe vera beverage in Pontianak, represented by 150 respondents using quota sampling techniques and then analyzed by the Quality Function Deployment (QFD) and Structural Equation Modeling (SEM) methods. The results of the analysis show that only design and quality affect the purchase resolution, with a model of preferences namely; 500 ml size packaging; lychee flavor; nutrients such as vitamins, minerals, enzymes and amino acids; the physiological benefits that can provide energy, nourish and prevent diseases of the body; and certification most important product is labeling halal. Manufacturers need to change the shape of the packaging glass into the shape of the bottle, increase the level of lychee flavor in the composition of the ingredients, include information about: nutrition, benefit, and product certification on the package label.Keywords: aloe vera beverage,model, purchase resolution, quality function deployment (QFD), structural equation modeling (SEM).